MATH
posted by kristie .
I need to simply this equation, but I got stuck.
h/(4sqrt(16+h)) = y
First, I multiplied (4+sqrt(16+h)/(4+sqrt(16+h) to both sides, and I ended up with h(4+sqrt(16+h)/h. Is this correct? (I tried to graph both equations to see if I would get the same graph, but I didn't, which means it's wrong.)
Please help me out!
h/(4sqrt(16+h))*(4+sqrt(16+h))/(4+sqrt(16+h))
h(4+sqrt(16+h))/4(16h)=
h(4+sqrt(16+h))/(12h)= then proceed. There is not much you can do.
Respond to this Question
Similar Questions

radical equation
2^x+20=15+3^x A)1 B)16 C)5 D)25 I chose c but i got it wrong i am having a problem understanding it. Let me rewrite the question in a more standard format. 2* sqrt(x)+20=15 + 3*sqrt(x) where * means multiply, and sqrt means the square … 
Algebra
Solve for s: h=(square root of 3)times s/2 and solve for h V= (pi)r squared h / 3 Solve for s: h=(square root of 3)times s/2 Multiply both sides by 2. 2h = (sqrt 3)*s*2/2 which cancels the 2 on the right. 2h = (sqrt 3)*s Now divide … 
Math(Roots)
sqrt(24) *I don't really get this stuff.Can somebody please help me? 
math,algebra,help
Directions are simplify by combining like terms. x radiacal 18 3 radical 8x^2 can someone show me how to do these types of problems. thanks I cant determine the second term. For the first, I think you meant x sqrt(18) which reduces … 
Mathematics
sqrt 6 * sqrt 8 also sqrt 7 * sqrt 5 6.92820323 and 5.916079783 So you can see the steps — sqrt 6 * sqrt 8 = sqrt 48 sqrt 7 * sqrt 5 = sqrt 35 I hope this helps a little more. Thanks for asking. 
Math Help please!!
Could someone show me how to solve these problems step by step.... I am confused on how to fully break this down to simpliest terms sqrt 3 * sqrt 15= sqrt 6 * sqrt 8 = sqrt 20 * sqrt 5 = since both terms are sqrt , you can combine … 
Math/Calculus
Solve the initialvalue problem. Am I using the wrong value for beta here, 2sqrt(2) or am I making a mistake somewhere else? 
maths
how do i solve this equation? 21(X(1/7))^2= 3/7 thx Divide both sides by 21 Take the square root of both sides. Rewrite it as x  (1/7)= sqrt [(1/21)*(3/7)] = sqrt[(1/7)*(1/3)(1/7)] = (1/7) sqrt(1/3) x = (1/7)[1 + sqrt(1/3)] tahnks 
Surds
Solve in the exact form. (sqrt of 4x+1)+(sqrt of x+1)=2 Someone showed me to do this next: Square both sides..so.. 4x+1+2((sqrt of 4x+1)•(sqrt of x+1))=4 I do not understand where the 2 come from ..and why do we need to multiply … 
Calculus check
Given f(x)=x^4(2x^215). On what interval(s) is the graph of f concave upwards?